2011
DOI: 10.1104/pp.111.177709
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Link betweenSTMandCUC1during Arabidopsis Development      

Abstract: The KNOXI transcription factor SHOOT MERISTEMLESS (STM) is required to establish and maintain the Arabidopsis (Arabidopsis thaliana) apical meristem, yet little is known about its direct targets. Using different approaches we demonstrate that the induction of STM causes a significant up-regulation of the organ boundary gene CUP SHAPED COTYLEDON1 (CUC1), which is specific and independent of other meristem regulators. We further show that the regulation of CUC1 by STM is direct and identify putative binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 58 publications
3
106
0
2
Order By: Relevance
“…The other class I KNOX genes are expressed and perform redundant, albeit weaker, functions compared with STM in the SAM, with BP/ KNAT1 and KNAT6 playing remarkable roles during flower gynoecium development (Arnaud and Pautot, 2014). Because the induction of class I KNOX genes can cause the up-regulation of CUC genes (Spinelli et al, 2011), future investigation is necessary to determine whether the elevated expression of CUC1, CUC2, and CUC3 is a secondary effect in the atzrf1a atzrf1b mutant. Within the SAM, WUS is expressed specifically in the stem cell organizing center and acts both independently and complementarily with STM in the maintenance of stem cell activity (Laux et al, 1996;Mayer et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The other class I KNOX genes are expressed and perform redundant, albeit weaker, functions compared with STM in the SAM, with BP/ KNAT1 and KNAT6 playing remarkable roles during flower gynoecium development (Arnaud and Pautot, 2014). Because the induction of class I KNOX genes can cause the up-regulation of CUC genes (Spinelli et al, 2011), future investigation is necessary to determine whether the elevated expression of CUC1, CUC2, and CUC3 is a secondary effect in the atzrf1a atzrf1b mutant. Within the SAM, WUS is expressed specifically in the stem cell organizing center and acts both independently and complementarily with STM in the maintenance of stem cell activity (Laux et al, 1996;Mayer et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…19,49 Although functionally connected, the expression of CUC1, CUC2 and CUC3 genes is regulated through different pathways. This is also reflected by their expression profiles, which are not identical in the SAM, 25,34,45 Fig. 1B In addition to transcriptional control, CUC1 and CUC2 are subjected to post-transcriptional regulation through the micro-RNA pathway.…”
mentioning
confidence: 99%
“…They play an essential role in shoot meristem initiation through the regulation of STM expression. 1,9,19,29,34,45,49 Recently it has been reported that CUC1 and CUC2 are also required for formation and stable positioning of the carpel margin meristems. 23 Depletion of these genes leads to defects in cotyledon separation, organ fusions and cup-shaped cotyledons.…”
mentioning
confidence: 99%
“…A recent report shows that SHOOT MERISTEMLESS (STM) acts as a direct activator of CUC1 through CTGTCA elements found in the CUC1 promoter (Spinelli et al, 2011). Prolonged ectopic expression of STM also leads to activation of CUC2 and MIR164A, but this effect is indirect (Spinelli et al, 2011).…”
Section: Pcg-mediated Repression At Several Levels Of Leaf Margin Devmentioning
confidence: 99%